The comparison of mental toughness in athlete men and women in individual contact and non contact sports - Kashani, V.; Farokhi, A.; Motesharee, E.; Mokaberian, M. (Electronic Physician, 2011)
Today an optimal performance athletic result is a combination of different factors. Mental toughness as one of the most important psychological characteristics related to outcomes and success in elite sport; so that most coaches and sport psychologists; beliefs mental toughness isthe most important psychological factor affecting the success of athletes. The aim of current studyis The comparison of mental toughness in athlete men and women in individual contact and noncontact sports. To determine sample size; first of all; a preliminary study were done with using180 male and female athletes in the three individual contact sports (Wushu, kickboxing, Taekwondo) And three non-contact sports (badminton, squash,tennis). At the end according to individual scores mean and variance and use formula of determine sample size with p value 95% and with power test 80%; 300 athletes were selected as the study sample. The sport mental toughness questioner (SMTQ) was used to measure athletes mental toughness. Two way ANOVA and Tukey post hoc test based on the significant level of alpha %5 were conducted for analyses Data. The results of this research indicated that main effect of gender, type of sport (contact and non-contact) were significant. However interaction effects of gender and type of Sport were notsignificant. The results of this research indicated that males scored significantly higher (p < 0.05) than females score in mental toughness this finding along with Adam R et al (2009) results. These differences could be due to variations in the underlying expression of the attributes related to MT in males and females or alternatively to different socialization processes. Our results revealed that there were significant differences among athletes who participate in contact or non contact sports, this finding along with Gray Khan and Jolierowy (2007) results, but not Adam R etal (2009 ) result. Possible causes of superior athletes that participate in contact sports than athletes who participate in non-contact sports must be searched in nature and philosophy of martial artsbased on physical and psychological stress. In addition experience violence in contact sports spiritual person to stand difficult living conditions and exercise more robust returns. Mental toughness is having the natural or developed psychological edge that predicts Athletes success. Exposure hard conditions (competition; exercise) can development MT. Various factors such as time situation, competitive experience, age, activity level, nature of sport and individual differences have important roles in shaping and creating good mental skills.